Hubungan Budaya Organisasi dengan Kinerja Perawat di Rumah Sakit Umum Insani Stabat Kabupaten Langkat - Iim Rudiansyah (KOLONI, 2022)
Strong organizational culture / positive can give the effect of influencing the behavior of individuals and then determines the performance of members and the organization. Generally speaking, there is strong and significant correlation between organizational culture and nurse's performance. Strong organizational culture / positive will create a commonality of interest, motivation, and control structures to shape the behavior needed to improve the performance of organizations that have an impact on the performance of nurses. Strong organizational culture / positive will provide stability to the organization that can boost the performance of nurses. This type of research using cross sectional study design research goal is to determine the relationship of organizational culture on performance of nurses at the General Hospital Insani Stabat 2016. Research will be conducted at the General Hospital Isani Stabat Langkat Year 2016. The sampling technique is done by using total population about 30 people. The results of hypothesis testing to see the relationship between the variables X and Y are variable with significance level (α) = 5% (0.05) and df = 1 result p.value = 0.000 at df = 1dimana sig <α (0.000 <0, 05) can be concluded H0 rejected and Ha accepted at the 5% significance level. So there is a relationship of organizational culture on performance of nurses in Hospital Insni Stabat. The results of this study are expected to provide input to the leadership in the hospital to design a policy that can foster a positive organizational culture so that it can improve the performance of nurses. Keywords: Organizational Culture, Performance